2020
DOI: 10.2147/ott.s230577
|View full text |Cite
|
Sign up to set email alerts
|

<p>DUB3 Facilitates Growth and Inhibits Apoptosis Through Enhancing Expression of EZH2 in Oral Squamous Cell Carcinoma</p>

Abstract: Background: Here, we probed the action mechanism of ubiquitin-specific processing proteases 17 (DUB3) in the evolution of oral squamous cell carcinoma (OSCC). Methods: The expression of genes were calculated by qRT-PCR, and proteins were assessed by Western blot and immunohistochemistry. The cells viability and proliferation were checked by MTT and EdU assay, respectively. Flow cytometry was implemented to detect the cell cycle and apoptosis. The activity of EZH2 gene promoter was measured by luciferase report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Therefore, EZH2 is considered a druggable target in metastatic UM. Furthermore, an increasing number of DUBs, including USP21 [135], UPS44 [136], and DUB3 [137], have been shown to deubiquitinate and stabilize EZH2, resulting in malignancy, which suggests that inhibition of various DUBs and subsequent degradation of EZH2 might be promising targeted therapies in UM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EZH2 is considered a druggable target in metastatic UM. Furthermore, an increasing number of DUBs, including USP21 [135], UPS44 [136], and DUB3 [137], have been shown to deubiquitinate and stabilize EZH2, resulting in malignancy, which suggests that inhibition of various DUBs and subsequent degradation of EZH2 might be promising targeted therapies in UM.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting BRD4 degradation, DUB3 enhanced the expression of EZH2 in OSCC, promoted cell growth and inhibited apoptosis. This indicates that decreasing DUB3 could inhibit OSCC cell proliferation and promote cell apoptosis (50,51). Overall, DUB3 stabilizes BRD4 through deubiquitination and promotes cancer progression, suggesting that DUB3 may be an effective anticancer target for cancer therapy.…”
Section: Ubiquitinationmentioning
confidence: 95%
“…A recent study reported that DUB3 binds to and promotes the deubiquitination and stabilization of BRD4 and protects prostate cancer cells from BETis by promoting BRD4 deubiquitination (43) (Figure 2). Other studies have shown that DUB3 is overexpressed in oral squamous cell carcinoma (OSCC) tissues and cell lines and is negatively correlated with patient survival time (50,51). By inhibiting BRD4 degradation, DUB3 enhanced the expression of EZH2 in OSCC, promoted cell growth and inhibited apoptosis.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…DUB3 is overexpressed in oral squamous cell carcinoma (OSCC) tissues and cell lines, and it has a negative effect on the survival of patients with OSCC. Mechanistically, DUB3 promotes the proliferation of OSCC cells and inhibits apoptosis by triggering the expression of enhancer of zeste homolog-2 (EZH2) by suppressing ubiquitin-mediated bromodomain-containing protein 4 (BRD4) degradation [ 37 ].…”
Section: Role Of Dub3/usp17 In Cancermentioning
confidence: 99%